Transforming Agriculture through AI: A Technical Perspective on Next-Generation Farming - Sandeep Reddy Pakeer, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the transformative impact of Artificial Intelligence in modern agriculture, examining the integration of advanced technologies across multiple domains including aerial surveillance, IoT infrastructure, soil analytics, and weather forecasting. The article investigates how AI-driven systems have revolutionized traditional farming practices through sophisticated computer vision, machine learning algorithms, and sensor networks. The article demonstrates significant advancements in crop monitoring, resource optimization, and risk management through the implementation of multi-layered architectural frameworks. The article encompasses various technological components including drone-based surveillance, soil monitoring systems, weather prediction models, and integrated decision support systems, highlighting their collective contribution to enhancing agricultural productivity and sustainability.
Keywords: Agricultural IoT Systems; Artificial Intelligence in Agriculture; Deep Learning for Crop Management; Precision Farming Technologies; Smart Agriculture Infrastructure